Entre movimentos e imagens: os poderes da alma na República de Platão - Diogo Norberto Mesti da Silva (2014)
The purpose of this dissertation is to analyze Plato´s psychology such as it is developed in book IV of the Republic, by pointing out the relations the different kinds of soul movement establish with the images of values. We focus on the relations between the forms of values (like virtues, justice, the good) and their images (eidola), icons (eikones), appearances (phantasmata) and paradigms (paradeigmata). Perceiving differences among these images is a necessary step towards the explanation of the relations between soul movements and forms, because only thus can one understand the different ways the soul has of reaching that which is a value in itself. We argue that, in the different dialectical moments in the Republic, the use of different types of images serves the purpose of pointing to different relations between soul movements and forms of values: the icons of the forms of virtue (book III), the image of justice (book IV) and the different kinds of images on the line and the cave (books VI-VII). Against the interpretation trends that isolate the different moments of the dialogue, we propose an integrating view, by articulating the use of images to the search for knowledge, based on the most recent research on the role of images in Plato´s thought. We argue that the central books in the Republic do not target at a theory of ideas which would be independent from the images that have been used along its development, but, instead, sustain the importance of a progressive acquaintance with the images of forms of values, in a reflexive process in which the importance of the movement of the soul becomes clear in the direction of forms.